Legal Uncertainty in Legal Protection for Notaries Holding Protocols from Notaries Making Protocols Who Have Died in Tegal City - Zamzuri, Mohamad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Notaries in carrying out their duties as notaries who hold protocols often receive criminal and civil lawsuits and complaints to the MPD due to defects in protocols made by other notaries who are notaries who make protocols. The type of research used in this article is sociological or empirical legal research which includes legal identification and legal effectiveness. Empirical legal research is legal research in which data is obtained through primary legal data or data obtained directly in society. Based on the study in this paper, it is understood that legal protection for Notaries holding protocols from Notaries making protocols who have passed away in Tegal City has not yet been realized optimally, this is shown by the fact that some people are still filing criminal and civil lawsuits against Notaries holding protocols when the protocol made by the Notary making the protocol who has died is known to be problematic.